ANTIHYPERTENSIVE, ORGAN PROTECTIVE, AND METABOLIC EFFICIENCY OF SPIRAPRIL IN PATIENTS WITH ARTERIAL HYPERTENSION - M. V. Leonova; M. A. Demidova; A. V. Tarasov; Y. V. Belousov (Столичная издательская компания, 2015)
Aim. To estimate antihypertensive, organ protective and metabolic efficiency of angiotensin converting enzyme (ACE) inhibitor spirapril in patients with arterial hypertension (AH). Material and methods. 30 patients with AH of I-II grade with different cardiovascular risk were included into the study. Spirapril was prescribed in the dose of 3 mg once daily. If necessary, daily dose could be increased to 6 mg after two weeks, and after next 4 weeks hydrochlorothiazide in daily dose 12,5-25 mg could be added. Treatment lasted 16 weeks. Before and after 16-week treatment ambulatory blood pressure monitoring (ABPM) was carried out. At the same time vasodilatation tests for reactive hyperemia and nitroglycerin were held, microalbuminuria and β2-microglobulinuria levels were defined, figures of lipid and glucose metabolism were studied, questionnaires for quality of life were filled in. Results. 27 patients with AH finished the study according to protocol. Treatment with spirapril within 16 weeks caused normalization of blood pressure in 60% of patients, decreased levels of microalbuminuria (p<0,05) and β2-microglobulinuria (p<0,05), recovered significantly disrupted endothelial function according to the results of vasodilatation tests (p<0,01), improved patients quality of life (p<0,05). Spirapril didn't change lipid and glucose metabolism, regardless that in 1/3 of cases it was used in combination with hydrochlorothiazide. Conclusion. Spirapril is a highly efficient antihypertensive drug with organ protective effect and metabolic neutrality. According to the revealed qualities it can be recommended to patients with AH with high cardiovascular risk.